MECHANISMS TO IMPROVE THE ACCESSIBILITY OF ADMINISTRATIVE COURT PROCEEDINGS IN RUSSIA AND UKRAINE - Aleksandrovna Trempolets, Lilia (Revista Inclusiones, 2019)
Comparative analysis of the current law, in particular, the Code of Administrative Judicial Procedure of the Russian Federation and the Code of Administrative Proceedings of Ukraine, is of great interest. Rationale. The relevance of the study is determined, first, by the scientific discussions and the absence of common opinion on the accessibility of administrative legal proceedings in Russia and Ukraine. The practice of administrative legal proceedings in Ukraine indicates that the absence of such provisions during the administration of justice causes judges to follow case law, clarifications from courts of higher jurisdiction, etc. rather than the provision of law. Moreover, the prospect of creation and operation of administrative courts in Russia is currently under debate. Purpose of the article. The purpose of this article is to elaborate the functional-legal approach that would determine the efficiency of the mechanisms that improve access to administrative court proceedings in Russia and Ukraine. Given the positive experience of the European Union countries, including Ukraine, in the field of administrative court operations, it is necessary to consider the feasibility of creating similar courts in Russia. Methods. The chief method that is the key to solving the problem is the inductive approach to examining the legal basis of the realization of the mechanisms that improve access to administrative court proceedings in Russia and Ukraine. Results. To sum up the conducted comparative legal analysis, it is worth noting, that the adopted Code of Administrative Judicial Procedure of the Russian Federation regulates administrative proceedings in a more clear and detailed way than the Code of Administrative Proceedings of Ukraine. The elaboration of the procedure for certain categories of cases in the Code of Administrative Judicial Procedure of the Russian Federation makes enforcement activities sufficiently easier.